PEMANFAATAN MEDIA SURAT KABAR SEBAGAI MATERIBAHASA INDONESIA DAN INTEGRASI KARAKTER - Muhammad Zakia Firdaus (FKIP, Universitas Billfath Lamongan, 2020)
The purpose of this study to describe 1) Use of discours Mimbar Jumat Solopos newspaper as material in Indonesian Language lesson 2) Know the character integartion discours Mimbar Jumat Solopos newspaper as material in Indonesian Language lesson. This type of research descriptive qualitative. The results of study show that wacana Mimbar Jumat can be used a resource materialsand there is charakter value